2023
DOI: 10.1038/s12276-023-00953-x
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of genetic muscle disorders induced by mutations in fast and slow skeletal MyBP-C paralogs

Abstract: Skeletal muscle, a highly complex muscle type in the eukaryotic system, is characterized by different muscle subtypes and functions associated with specific myosin isoforms. As a result, skeletal muscle is the target of numerous diseases, including distal arthrogryposes (DAs). Clinically, DAs are a distinct disorder characterized by variation in the presence of contractures in two or more distal limb joints without neurological issues. DAs are inherited, and up to 40% of patients with this condition have mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 121 publications
(179 reference statements)
0
10
0
Order By: Relevance
“…2D; Table 2), suggesting that fMyBP-C impacts lattice order across SLs potentially via thin filament interactions 21,28 . sMyBP-C and fMyBP-C have well-characterized structural differences in their N-termini, yet differences in functionality are still not fully described 19,30 . With only sMyBP-C in the C2 -/- fibers and a mix of MyBP-C isoforms in the NTG, our results for d 1,0 and σ D suggest that sMyBP-C supports or allows a greater radial distance between myofilaments compared to fMyBP-C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2D; Table 2), suggesting that fMyBP-C impacts lattice order across SLs potentially via thin filament interactions 21,28 . sMyBP-C and fMyBP-C have well-characterized structural differences in their N-termini, yet differences in functionality are still not fully described 19,30 . With only sMyBP-C in the C2 -/- fibers and a mix of MyBP-C isoforms in the NTG, our results for d 1,0 and σ D suggest that sMyBP-C supports or allows a greater radial distance between myofilaments compared to fMyBP-C.…”
Section: Resultsmentioning
confidence: 99%
“…1A) with the C'-terminus bound to the thick filament (C8-C10), and the other N'-terminal domains (C1-C7) pointed away from the thick filament, most likely interacting with myosin heads and the thin filament 22,23,28,29 . Skeletal muscles contain fast (fMyBP-C) and slow (sMpBP-C) isoforms that may function differently and are not necessarily fiber-type specific 19 . It was recently shown that rapid removal of the C1-C7 domains of fMyBP-C in the fast-twitch dominant psoas muscle led to an SL-independent movement of myosin heads towards the ON state, but the SL-dependent transition of myosin heads towards the ON state at longer vs. shorter SLs was largely intact 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in the skeletal muscle paralogs lead to debilitating myopathies in humans including severe and lethal forms of distal arthrogryposis myopathy 10,11 and lethal congenital contracture syndrome 9 , suggesting a critical role in healthy sarcomere function. In addition, fMyBP-C knockout mice present altered force generation with myosin heads (i.e., free-heads) shifted towards the ON state 9,26 , suggesting that MyBP-C helps stabilize the myosin OFF state and/or suppresses OFF-to-ON transitions 2628 . Importantly, MyBP-C effects can be blunted via post-translational modifications such as phosphorylation 2931 , which can be altered in some myopathies but also in healthy muscle during exercise, e.g., via increased PKA/PKC activity 32 .…”
Section: Figmentioning
confidence: 99%
“…Myosin binding protein C (MyBPC) is an essential regulator of contractile function in skeletal and cardiac muscle ( Bennett et al, 1999 ; Oakley et al, 2004 ; Heling et al, 2020 ; Song et al, 2023 ). Initially, MyBPC was visualized as an unknown thick filament structure in frog sartorius muscle via low-angle X-ray diffraction experiments and stripes of extra mass 43 nm apart in long sections of muscle ( Huxley, 1967 ; Huxley and Brown, 1967 ).…”
Section: Introductionmentioning
confidence: 99%